Inadvertent Entrapment of a Central Venous Catheter by a Purse-String Suture during Cardiopulmonary Bypass: A Case Report. (18th December 2011) - Anvaripour, Abdorasoul; Yazdanian, Forouzan; Totonchi, Mohammad-Zia; Shahryari, Houshang
Abstract : A 65-year-old female patient with severe mitral valve stenosis plus coronary artery disease was scheduled for mitral valve replacement and 2-vessel coronary artery bypass graft (CABG) surgeries simultaneously. After a successful procedure, resistance was met on a CVC withdrawal. During postoperative fluoroscopy, fixation of the catheter at the heart was confirmed which necessitated reopening the chest, cutting the suture, and removing the catheter. When a catheter became hard to withdraw after open heart surgery, we should never withdraw it forcefully and blindly. Although rare, one should consider inadvertent entrapment of CVC by a suture as the possible cause.